Analisis Penyebab Remaja Putus Sekolah Usia 15 Tahun ke Atas di Kelurahan Waioti - Trisnawati Bura; Nur Sakinah; Fransiska Andrea Poa; Elisabet Gustina Nesti; Yoseph Hendra; Elisabeth Bela (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research aims to analyze and determine the causes of teenagers dropping out of school at the age of 15 years and over in Waioti Village. This research is descriptive in nature. Based on the implementation method, this research is classified as survey research. In survey research, samples are taken from one population and a list of questions is used as a data collection tool. The survey research method was used because not all members of the population were used as examples or samples, so only some members of the population were used as samples. The sampling technique in this research used purposive random sampling. The population in this study were families whose teenagers had dropped out of school in Waioti sub-district. Based on the results of the interviews and discussion above, it can be concluded that teenagers drop out of school in Waioti sub-district due to several factors. Among the factors that cause teenagers to drop out of school are 1) economic and family factors, these two factors greatly influence teenagers' problems in finding work because financial limitations in the family and instability in the family environment will cause teenagers to drop out of school. 2) educational distance greatly influences the causal factors. teenagers dropping out of school, 3) inadequate educational facilities which prevent teenagers from continuing to a higher level.